Pendampingan Sertifikasi Halal untuk UMKM: Studi Kasus Bisnis Jeruk Peras Ibu Murniati di Desa Sidomukti - Zulaikah; Aziz, Saddam; Harida, Lisa; Sanifah, Hani Ulia; Sarmila (WISE Pendidikan Indonesia, 2024)
This study examines the implementation and impact of a halal certification assistance program for micro, small, and medium enterprises (MSMEs), focusing on a case study of the Jeruk Peras business owned by Ibu Murniati in Sidomukti Village, South Lampung. Many MSMEs face obstacles in obtaining halal certification due to a lack of awareness regarding the necessary procedures, insufficient access to structured information, and limited resources in terms of time, finances, and personnel. Using a qualitative descriptive method, the research documents the stages of mentoring, which include legal and administrative guidance, the creation of halal logos, product photography, and technical support for submitting online certification forms. The results show that this structured assistance significantly improved the participant’s understanding of the halal certification process and enabled independent submission of documentation. Furthermore, the program contributed to empowering local businesses by increasing their marketability, enhancing consumer trust, and reinforcing compliance with halal standards. This case demonstrates the importance of targeted educational and administrative support for MSMEs to reduce barriers in certification processes and promote inclusive economic growth.